“Liver–gut” axis: A target of traditional Chinese medicine for the treatment of non-alcoholic fatty liver disease - Guo, Kangxiao; Xu, Sisheng; Zeng, Zhaofeng (Frontiers in Endocrinology, 2022)
Nonalcoholic fatty liver disease (NAFLD) is a disease in which fat accumulates in the liver without excessive alcohol intake. Among the current approaches for the treatment of NAFLD, lifestyle modification with dietary changes and regular exercise are the mainstay treatments。With the rise of intestinal microecology, regulating the "liver-gut" axis can be an effective treatment for NAFLD.This review aims to assess modulation of Liver-gut microbiota axis as a TCM for the treatment therapeutic approach for treating NAFLD and further explores its application in the newly discovered therapeutic avenues beyond treatment for NAFLD.